1995
DOI: 10.1007/bf01857702
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial adaptation to stoma surgery: A review

Abstract: During the last decade strong improvements have been made in the medical care of patients with a digestive tract stoma, particularly with regard to nursing skills and to the quality of collecting material for faecal products. Scientific investigation into the psychosocial adjustment of patients after stoma surgery has intensified as well, giving us indications for quality of life. These developments induced a review of the actual state of affairs in psychological issues. After evaluating the results of psychos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 37 publications
1
44
0
1
Order By: Relevance
“…Fifty-two of 69 patients (75 percent) reported previous surgery for incontinence (with a median 2 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] operations in these 52 people). Of these, 34 reported previous anal sphincter repair, 17 previous postanal repair, 15 surgery for rectal prolapse, and 6 other operations.…”
Section: Previous Incontinence Historymentioning
confidence: 99%
“…Fifty-two of 69 patients (75 percent) reported previous surgery for incontinence (with a median 2 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] operations in these 52 people). Of these, 34 reported previous anal sphincter repair, 17 previous postanal repair, 15 surgery for rectal prolapse, and 6 other operations.…”
Section: Previous Incontinence Historymentioning
confidence: 99%
“…12 T he medical literature abounds with articles proclaiming the presumed negative impact that ostomies have on quality of life. [1][2][3][4][5][6][7] In some studies, [8][9][10][11] generic quality of life (QOL) instruments have demonstrated differences between individuals with and without a stoma. Other studies have indicated that a generic measure is not sufficiently specific to identify differences in the impact of a stoma on patient QOL.…”
mentioning
confidence: 99%
“…As to procedures involving the digestive system, Thomas [29] found that dif®culties in coping with the stoma was a greater determinant of later psychiatric disturbance than in coping with the underlying cancer. Bekker et al [30] reviewed the literature and concluded that technical improvements in stoma care did not result in a decline of psychosocial problems after surgery.…”
Section: Procedures Resulting In a Stomamentioning
confidence: 98%